1987
DOI: 10.1038/ki.1987.96
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intramuscular and intraperitoneal deferoxamine for aluminum chelation

Abstract: As intravenous administration of deferoxamine is difficult in home dialysis patients we set out to determine the efficacy of intramuscular (i.m.) and intraperitoneal (i.p.) deferoxamine for removal of aluminum. Patients with serum aluminum levels greater than 90 micrograms/liter were studied in a paired fashion with each patient serving as their own control. Serum and peritoneal fluid aluminum were determined using flameless atomic absorption. In hemodialysis patients 2 g of intravenous deferoxamine increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is clear from silver-staining techniques and electron microscopic studies that Al induces normally present protein subunits in neurons to assemble into masses of organized filaments. It has been demonstrated that the process of NFT formation can be partially reversed by initiating intramuscular desferroxamine (a metal chelator) treatment, even after the process of NFT has begun [63]. Al-induced neurofibrillary degeneration in rabbits is accompanied by reduction in serotonin and noradrenaline.…”
Section: Al and Nftsmentioning
confidence: 99%
“…It is clear from silver-staining techniques and electron microscopic studies that Al induces normally present protein subunits in neurons to assemble into masses of organized filaments. It has been demonstrated that the process of NFT formation can be partially reversed by initiating intramuscular desferroxamine (a metal chelator) treatment, even after the process of NFT has begun [63]. Al-induced neurofibrillary degeneration in rabbits is accompanied by reduction in serotonin and noradrenaline.…”
Section: Al and Nftsmentioning
confidence: 99%
“…1 (33,40); alternatively, aluminumaffected progenitors may not readily proliferate in vitro, or their progeny may be lost due to changes in membrane fragility (17,22). Although aluminum has been detected in erythrocytes (46,47), it has not been found in normoblasts of marrows from aluminum-intoxicated patients (20). Direct specific toxicity and/or interference at the cellular membrane remain possible mechanisms of aluminum-transferrin inhibition, and require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Desferrioxamine lacks oral efficacy, so is given by iv, im, or ip injection (Molitoris et al, 1987). This is one of the main driving influences behind the search for alternative chelators.…”
Section: Aluminum Chelation Therapymentioning
confidence: 99%